(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the effectiveness of the online medical appointment registration system at the On-demand Outpatient Department, 108 Military Central Hospital. Methods: A cross-sectional descriptive study was conducted on 445 patients using either online or traditional registration methods from August 2025 to September 2025 at the On-demand Outpatient Department, 108 Military Central Hospital. Results: The male-to-female ratio was approximately 1:1; the predominant age group was 31-40 years (28.8%). Most participants had a college/university education (68.8%) and a monthly income of 10-15 million VND (40%). Online registration was the most commonly used method (48.1%). The main reason for choosing this method was its convenience and speed (73.4%), with the most notable benefit being the ability to register anytime and anywhere (99.5%). However, 21% of patients experienced difficulties when using the system, mainly related to registration procedures (37.4%). Patients using online registration reported significantly higher satisfaction compared to those using traditional methods (p < 0.05). Conclusion: The study demonstrates that the online medical appointment system has a high utilization rate and significantly higher patient satisfaction compared to traditional methods (p < 0.05). Convenience and time-saving are the key factors influencing patient choice. However, some patients still encounter difficulties in system use, and awareness of data security remains limited. Further optimization and user support are needed to improve system effectiveness.